3-Nitramino-6-hydroxy-1, 2, 4, 5-tetrazine and its alkaline earth metal salts: an effective strategy to balance energy density and safety of energetic compounds. Issue 1 (2nd January 2021) - Ren, Jie; Zhang, Weijing; Zhang, Tianhe; Yin, Yanli; Wang, Lin; Li, Zhimin; Zeng, Qingxuan; Zhang, Tonglai
ABSTRACT: 3-Nitramino-6-hydroxy-1, 2, 4, 5-tetrazine (NHTZ) and its alkaline earth metal salts (Mg 2+ (1 ), Ca 2+ (2 ), Sr 2+ (3 ), Ba 2+ (4 )) were prepared via 3, 6-dinitramino-1, 2, 4, 5-tetrazine for the first time. The electrostatic potentials and HOMO-LUMO orbitals of them were computed to better understand the electronic structure of NHTZ. Structures of the four alkaline earth metal salts were confirmed by elemental analysis, IR spectroscopy, and single-crystal X-ray diffraction. Structural analysis revealed that all compounds have differently dimensional structures, increasing with the radius of metal atoms. Compounds 3 and 4 can be classified as coordination polymers due to their structural features. As the only 3D polymeric structure in this series, compound 4 possesses the highest density and best thermal stability in these compounds. Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) measurement shows the excellent thermal stability of these salts, with the thermal decomposition temperatures of 291.1°C (1 ), 294.1°C (2 ), 294.9°C (3 ) and 324.7°C (4 ). Heat of formation and sensitivity of the four salts were investigated, which suggest 4 as a potential heat-resistant energetic compound instructions for authors.